Monetary Policy and Borrowers' Loan Defaults: Research Based on Data from Renrendai. Issue 1 (16th February 2020) - Song, Wenda; Zhang, Haiyang
Abstract: This paper uses Renrendai data to study the relationship between monetary policy and the default behavior of borrowers, and analyzes the transmission channels. The research shows that tight monetary policy will lead to a significant increase in a borrower's probability to default, and this effect will continue for several months. There may be two transmission channels: (i) monetary policy changes a debtor's liquidity through credit and balance sheet channels, which directly affects their current repayment behavior; and (ii) monetary policy may affect a borrower's investment, production and profitability, thus changing their long‐term solvency. The paper also finds that the repayment behavior of productive borrowers is more susceptible to monetary policy than consumptive borrowers, and that the default behavior of borrowers in coastal provinces is more susceptible to monetary policy than of borrowers in inland provinces. These findings provide new evidence for understanding how monetary policy affects individual behavior and its transmission mechanisms.